Simplified modelling method to predict output speed of an overrunning clutch using ADAMS/Solver subroutine - Imran, M.N. (Asian Research Publishing Network, 2016)
A study on working principle of an overrunning clutch was conducted and a set of simplified mathematical equation was derived for different working conditions of the mechanism. This paper presents a method of simplified modelling to predict the output speed by applying the derived mathematical equations using user-written subroutine in ADAMS/Solver. The model was assumed to have negligible slipping torque and static friction. The subroutine written and compiled in C++ language using Microsoft Visual Studio is programmed for the modelling of the simplified model in ADAMS/View to simulate the mechanism. A model of an overrunning clutch using actual dimensions including rollers was modelled and simulated using ADAMS/View for comparison purposes. The average magnitude of output speeds was found to be identical but the trends were slightly different due to slipping torques. Â© 2006-2016 Asian Research Publishing Network (ARPN).